Determinan Nilai Perusahaan dengan Kepemilikan Institusional Sebagai Variabel Moderating - Baihaqi Ammy; Puja Rizqy Ramadhan (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
This research aims in general to produce a determinant model of corporate value with institutional ownership as a moderating variable in banking companies listed on the Indonesia Stock Exchange. The sample in this study is all public banking sector companies listed on the Indonesia Stock Exchange (IDX) which number 43 companies The type of data used in this study is using primary data. The results showed that variable returns on assets had a positive but insignificant effect on the company's value variables. Non-performing loan variables negatively and significantly affect the company's value variables. Variable capital adequacy ratio has a positive and significant effect on the variable value of the company. Variable loan to deposit ratio negatively and insignificant to the variable value of the company. Variable operating costs to operating income have a positive but insignificant effect on the company's value variables. Institutional ownership variables are unable to moderate the effect of variable return on assets, non performing loans, capital adequacy ratios, loan to deposit ratios and operating costs on operating income against the company's value.